The prognostic value of p16ink4a marker in the diagnosis of cervical dysplasia - E. A. Dyadyk; Yu. I. Pokolodnaya (Patologìâ)
The morphological study of 110 cervical biopsies from patients with suspected cervical intraepithelial neoplasia (dysplasia) was performed with the help of immunohistochemical method using marker р16ink4a. This method confirmed the diagnosis of dysplasia, made after histological study, only in 56% of patients. Thus, for better assessment of the presence and degree of dysplasia of cervical epithelium it is advisable to include an identification of cyclin kinase inhibitor р16ink4a in the diagnostic algorithm.